Strategy For Choosing A College To Continue Further Studies For Students In Batubara Regency - Sulistyawati, Sri; Alamsyah, Bhakti; Sofiyan, Sofiyan; Tua Siregar, Robert; Setyawan, Iwan (International Journal Of Community Service, 2025)
College is a more complex gateway and focuses on a particular field of expertise. Therefore, it is only right that in finding a college there are many measuring indicators, depending on the priorities of each individual. Although education is not only obtained in the classroom, the way to explore students' potential needs to be done because the world of work which is a phase of life that actually depends on what they currently have. The Community Service that we carried out in Batubara Regency in collaboration with the Regional Education Office Branch V of Batubara Regency, the event "Socialization of Strategies for Choosing a College to Continue Further Studies for Students in Batubara Regency" went well and there was a very high-quality two-way interaction from the interaction it was revealed that this socialization event provided information and guidance to students so that they could make the right decision about the college they wanted to enter In the event, students and principals got an overview and additional insight that college or higher education is a further stage after completing high school (SMA) or equivalent. In college, a person will gain deeper knowledge and understanding about the field of interest. However, there are still many of us who do not understand the importance of college. The methods used in this activity are lectures, discussions, and questions and answers about problems related to the Socialization of Strategies for Choosing a College to Continue Further Studies for Students in Batubara Regency. In this socialization event, participants held discussions and listened to socialization lectures that were packaged in the form of power point slide sheets and videos so that they could understand and comprehend the Strategy for Choosing a College to Continue Further Studies for Students. This is planned to be carried out continuously for this stage will be carried out within 1 year.